2022
DOI: 10.3389/fmed.2022.973030
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and outcomes of acute kidney injury among COVID-19 patients: A systematic review of systematic reviews

Abstract: The COVID-19 associated acute kidney injury (CAKI) has emerged as a potential intricacy during the management of patients. Navigating the rapidly growing body of scientific literature on CAKI is challenging, and ongoing critical appraisal of this complication is essential. This study aimed to summarize and critically appraise the systematic reviews (SRs) on CAKI to inform the healthcare providers about its prevalence, risk factors and outcomes. All the SRs were searched in major databases (PubMed, EMBASE, Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…11,23 Recent reviews and meta-analyses that include many studies of the early pandemic period reported the following ranges: 28% to 34% 11,14,15,40 prevalence of overall AKI, 46% to 77% prevalence of AKI in ICU patients, 11,14,40 and 2.55 to 23.09 for OR for mortality. 41 Furthermore, in a study of AKI in COVID patients during all of 2020, HR (95% CI) for mortality was 3.8 (3.24-4.45), and mean LOS was 10.4 days. 42 Among COVID patients admitted to UK hospitals in 2020, the adjusted OR (95% CI) for in-hospital mortality was 1.91 (1.82-2.01) for biochemically determined AKI (vs no AKI), 2.41 (2.20-2.64) for stage 2 AKI, and 3.50 (3.14-3.91) for stage 3 AKI.…”
Section: Discussionmentioning
confidence: 99%
“…11,23 Recent reviews and meta-analyses that include many studies of the early pandemic period reported the following ranges: 28% to 34% 11,14,15,40 prevalence of overall AKI, 46% to 77% prevalence of AKI in ICU patients, 11,14,40 and 2.55 to 23.09 for OR for mortality. 41 Furthermore, in a study of AKI in COVID patients during all of 2020, HR (95% CI) for mortality was 3.8 (3.24-4.45), and mean LOS was 10.4 days. 42 Among COVID patients admitted to UK hospitals in 2020, the adjusted OR (95% CI) for in-hospital mortality was 1.91 (1.82-2.01) for biochemically determined AKI (vs no AKI), 2.41 (2.20-2.64) for stage 2 AKI, and 3.50 (3.14-3.91) for stage 3 AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these patients require KRT, increasing the resources needed for care and evolving greater morbidity and mortality. Measures to prevent the occurrence or progression to a more severe progression of AKI are fundamental [ 26 , 27 ]. Thus, early prognostic assessment and risk stratification measures that support clinical decisions in allocating appropriate resources and early interventions to each patient have the potential to enhance personalized hospital care and to help reduce morbidity and mortality rates [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, there have been a few reviews on extrapulmonary manifestations [8,[10][11][12][13], but the types of complications and their overall effect on hospitalization and mortality rates have never been explored. In addition, a large number of reviews exist on manifestations in individual organ systems of the body [14][15][16][17][18][19], but no study has ever attempted to gather information in a single article through extensive research on major organ systems. Furthermore, there are other infections that can cause atypical complications, i.e., dengue and Varicella-Zoster virus infections are well known to cause dementia, chronic encephalitis, aseptic meningitis, multiple sclerosis, acute pancreatitis, and myopericarditis [20][21][22][23][24][25] and such complications further accelerate patient hospitalization and rates of morbidity and mortality, which, in turn, render a huge burden on the healthcare system.…”
Section: Introductionmentioning
confidence: 99%